Numerical Analysis of the Damage Evolution in a Composite Pipe Joint Under Cyclic Static Axial Tension - Figiel, Ł.; Kamiński, M. (Engineering Transactions, 2003)
The main goal of this paper is to present a computational analysis of damage evolution in adhesive joint connecting composite pipes subjected to cyclic static axial tension with constant amplitude. The approach uses the simplified average shear stress criterion for defect propagation in the adhesive layer and applies the continuum damage mechanics concept to continuum crack-like damage representation in terms of the finite element stiffness. Numerical studies are performed using the commercial Finite Element Method displacement-based ANSYS program, with its special purpose finite element containing birth and death option. Computed damage evolution per a loading cycle leads further to estimation of the cumulative damage growth in terms of a crack-like type for different load amplitude levels. Finally, a numerically determined relation between the applied load amplitude and the load cycles number to failure is derived.